Design of Practical Tools for Achievement of ¾ PK Split AC Cooling System Laboratory Scale Dian Nusantara University - Anggananda Diamond; Komarudin; Denny Prumanto; Taufik Nur Isman; Ilham Syawwal Luthfi (Greenation Research & Yayasan Global Resarch National, 2026)
This design aims to design and build a laboratory-scale refrigeration test tool that can be used to test the performance of a cooling system under various operational conditions.The design process for this test equipment involves several stages, from requirements analysis and mechanical and electronic design to fabrication and testing. Some of the features implemented in this equipment include precise temperature control, a digital monitoring system, and the ability to test various types of refrigeration systems. The expected outcome of this test equipment is the ability to provide accurate data on refrigeration system performance, which can then be used to improve energy efficiency and cooling system performance in industrial applications.